Hepatocellular carcinoma as predominant cancer subgroup accounting for sex differences in post-hepatectomy liver failure, morbidity and mortality. Issue 9 (September 2022) - De la Cruz Ku, Gabriel; Aizpuru, Matthew; Hackl, Hubert; Ubl, Daniel S.; Habermann, Elizabeth B.; Pery, Ron; Driedger, Michael; Assinger, Alice; Nagorney, David M.; Cleary, Sean P.; Smoot, Rory L.; Starlinger, Patrick
Abstract: Background: Experimental evidence suggests sex dependent differences in liver regeneration. Limited evidence is available examining sex differences in post-hepatectomy liver failure (PHLF) and postoperative outcomes. Our aim was to assess the influence of sex on the outcomes after liver resection. Methods: The hepatectomy targeted National Surgical Quality Improvement Program (NSQIP) database was assessed for associations between sex and outcomes. Results: A total of 13, 401 patients underwent elective hepatic resection between 2014-2017. PHLF was highest among male patients with hepatocellular carcinoma (HCC) (OR = 2.81, 95%CI:1.40–5.62). Male sex was independently associated with increased PHLF (OR = 1.47, 95%CI:1.15–1.88), major complications (OR = 1.25, 95%CI:1.08–1.45), mortality (OR = 1.61, 95%CI:1.03–2.50), and if only major resections were assessed (OR = 1.38, 95%CI:1.03–1.84). Diagnosis specific subgroup analyses revealed that effects of sex were predominantly HCC associated. Conclusions: This is the largest series investigating the effects of gender on outcomes after hepatic resection. We documented that women undergoing liver resection have significantly lower risk of PHLF. This difference seemed influenced by the striking increase of PHLF in male HCC patients. These hypothesis suggest that sex might play a role in preoperative risk stratification.